Twenty-years journey of sustainable human resource management research: A bibliometric analysis - Shaha Faisal (Administrative Sciences, 2023)
Sustainability is gaining acceptance worldwide, and HRM is also influenced by it. Researchers globally are also exploring sustainable human resource management which creates a direct link between HRM and sustainability. Bibliometric analysis examined 247 documents on sustainable human resource management from 2003 to 2022. This study aimed to analyze the research trend, global distribution, contributory journals, leading authors, and contributing nations in sustainable HRM. In this bibliometric analysis, 247 documents have been analyzed. The review revealed that sustainable HRM is still an emerging concept worldwide; more researchers from European and Asian countries dominate this field. The present review will be helpful for academicians, practitioners, and researchers in this field. The study also presents interesting results that could help line managers and top managers to formulate ideas for sustainable HRM practices in their own companies.
Keywords: 350; bibliometric; environment; HRM; sustainability; sustainable human resource management